Moisture robustness of eaves solutions for ventilated roofs: Experimental studies. (21st October 2019) - Grynning, Steinar; Asphaug, Silje Kathrin; Gullbrekken, Lars; Time, Berit
Abstract : Ventilated pitched wooden roofs with eaves (roof overhangs) is a common building practice in Scandinavian countries. The eaves construction should be designed such that the least possible amounts of rainwater and snow enter the ventilation aperture between the roof cladding and the underlayment. Additionally, ventilation of the roof must be ensured to promote the proper drying-out capabilities of the roof and avoid snow melt and ice formation at eaves and gutters. Small or almost nonexisting eaves are a trend in modern architecture. It is a common perception that such solutions are more vulnerable to moisture damages. The aim of the study is to experimentally investigate the moisture robustness and to find answers to how the design of eaves influences the amount of rain that is driven into the apertures in ventilated roofs. This study observed that the amount of collected water is determined by the water droplet size and wind velocity inside the air cavity. This study simulates a rain event with heavy rain intensity and strong winds. The test represents an example of a storm event with a given droplet size distribution. The results indicate that an increased pressure drop decreases the water ingress.